Computer Simulation For Enhancing Gear Production Line With Flow Smoothing - Pruksaphanrat, Busaba; Kongcharoen, Keeradee; Suksamai, Prakaikan (Srinakharinwirot University Engineering Journal, 2025)
This research aims to find ways to smooth the flow of the production line, which produces 11 product groups of gears that involve both manual labor and semi-automatic machinery and have the production line with one-piece flow and job shop configurations. Currently, this production line cannot meet customer demand. Therefore, computer simulation was used to assist in the analysis of the improvement methods. The improvement of the gear production line involved adjusting batch sizes, prioritizing jobs with the Shortest Processing Time (SPT) considering the bottleneck stations, increasing resources, and employing various methods together. Experimental results showed that the most effective methods were adjusting batch sizes and prioritizing jobs with SPT together, resulting in a 37.30% increase in gear production rate, a 15.42% and 15.41% increase in employee and machine utilizations, leading to an improvement in production line efficiency 6.86%.